2016
DOI: 10.1186/s13287-016-0402-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential TLR activation of murine mesenchymal stem cells generates distinct immunomodulatory effects in EAE

Abstract: BackgroundRecently, it has been observed that mesenchymal stem cells (MSCs) can modulate their immunoregulatory properties depending on the specific in-vitro activation of different Toll-like receptors (TLR), such as TLR3 and TLR4. In the present study, we evaluated the effect of polyinosinic:polycytidylic acid (poly(I:C)) and lipopolysaccharide (LPS) pretreatment on the immunological capacity of MSCs in vitro and in vivo.MethodsC57BL/6 bone marrow-derived MSCs were pretreated with poly(I:C) and LPS for 1 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…Furthermore, it should be remarked that exposure to LPS and poly I:C does not have exactly the same immunological consequences. For example, they have different qualitative or quantitative effects on T cell proliferation, cytokine production, types of cells recruited, and inflammatory mediators produced, and they have different effects on plasma and brain cytokine levels in the fetuses …”
Section: The Maternal Immune Activation Model and The Consequences Fomentioning
confidence: 99%
“…Furthermore, it should be remarked that exposure to LPS and poly I:C does not have exactly the same immunological consequences. For example, they have different qualitative or quantitative effects on T cell proliferation, cytokine production, types of cells recruited, and inflammatory mediators produced, and they have different effects on plasma and brain cytokine levels in the fetuses …”
Section: The Maternal Immune Activation Model and The Consequences Fomentioning
confidence: 99%
“…Recent work demonstrated that heat inactivated MSC that lost their capacity to secrete factors maintain their immunomodulatory capacity after intravenous infusion in an LPS-induced sepsis model, suggesting that cell membrane dependent interactions with immune cells are responsible for the immune regulatory effects 18 . MSC express immunomodulatory molecules on their membrane such as Toll-like receptors (TLRs) 19 , ATPases 20 and CD73 (ecto-5′-nucleotidase, Ecto5′NTase) which dephosphorylate ATP into AMP and AMP into adenosine, respectively 21 . This is an important immunomodulatory function as adenosine has immunosuppressive properties 22 .…”
Section: Introductionmentioning
confidence: 99%
“…5 days after EAE induction and clinical score and animal weight was recorded daily for 22 days. Clinical scores were calculated as previously described ( 38 ). Blood samples were collected from mouse tail veins at day 18 after EAE induction and the plasma was obtained after centrifugation (300 × g , 20 min).…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme-linked immunosorbent assay (ELISA) for GM-CSF and the Enzyme Immunoassay kit for PGE2 (R&D Systems, USA) were used following manufacturer’s instructions with MSCs supernatants from cells activated or not with proinflammatory cytokines. NO 2 production was quantified in the supernatants of MSCs cocultured with Th17 cells for 5 days, using a modified Griess reagent (Sigma-Aldrich) as previously described by our group ( 38 , 39 ).…”
Section: Methodsmentioning
confidence: 99%